BOOK REVIEW: BEYOND BORDERS: NOTES ON THE COLONIAL AND POST-COLONIAL DYNAMICS IN THE AMERICAS, EUROPE AND INDONESIA - Novita Dewi (Sanata Dharma University, 2017)
Beyond Border is an inside look of what people across the globe have done for a long time. They all find themselves constantly engaged in action, reaction and interaction. The book answers the question of what colonial and postcolonial society has in common, i.e. crossing border.